Waldenström macroglobulinemia presenting as a renal or perirenal mass: Clinical and radiographic features - Moore, D.F.; Moulopoulos, L.A.; Dimopoulos, M.A. (Leukemia and Lymphoma, 1995)
Manifestations of macroglobulinemic lymphoma include lymphadenopathy, splenomegaly and bone marrow involvement. Renal presentations are unusual and complications of renal function are even less frequent. A review of all patients diagnosed with Waldenström macroglobulinemia at our institution from January 1987 to December 1993, revealed 4 cases (6% with renal presentations. We describe these cases with their associated clinical and radiologic features. © 1995 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.
Keywords: Computed tomography; Kidney; Lymphoma; Macroglobulinemia; Perirenal; Renal; Waldenström